The Mediating Role of Social Integration on the Effect of Proactive Socialization Tactics Applied by Newcomers on Their Organizational Commitment - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
The purpose of this study is to examine the impact of proactive socialization tactics applied by newcomers and social integration on organizational commitment, additionally, to analyze whether social integration has a mediating role between proactive socialization tactics and organizational commitment relationship. For this aim, in the theoretical part, proactive socialization tactics, social integration, and organizational commitment are explained. In the application part, a questionnaire including the measures of the proactive socialization tactics, social integration and organizational commitment is distributed to newcomers working in different sectors in Istanbul, Turkey. It is found that proactive socialization tactics applied by newcomers and social integration have a positive impact on organizational commitment, and social integration has a mediating role between the relation proactive socialization tactics and organizational commitment. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Proactive socialization tactics; social integration; organizational commitment; INFORMATION-SEEKING; ADJUSTMENT; BEHAVIOR; OUTCOMES; VALIDITY; ENTRY; MODEL